Acúfeno y umbrales auditivos en los rangos convencional y extendido de alta frecuencia. - Maggi , Ana Luz; Hinalaf , María; Gaetán , Sara; Muratore, Jimena; Kogan , Pablo; Hüg , Mercedes Ximena; Pérez Villalobo, Jorge Alejandro (Universidad Tecnológica Nacional., 2018)
The aim of this study was to analyze the presence and absence of tinnitus in relation to hearing thresholds in the conventional and extended high frequency ranges in adolescents. The sample was 259 adolescents. Hearing thresholds in the conventional and high frequency ranges were evaluated. Minor hearing thresholds in the extended range of high frequency in the ears with tinnitus were observed. The difference is increased in the group with higher thresholds, mainly at frequencies 11200 to 16000 Hz. It is necessary to continue investigating this problem in this particular age group because of the differences found in the extended high frequency range.
Keywords: Acúfeno; Umbrales auditivos; Alta Frecuencia; Adolescentes